THE RESPECT SCORE. THE DEMAND FOR RECOGNITION IN YOUTH SUBJECTIVITIES - Martínez, Darío Gabriel (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
In this paper I try to reflect on the claim for respect and recognition that students make to the scholar actors. Empirical references focus on students´ assertions who attend Schools and Youth and Adult Education Centers, placed in La Plata, Argentina. Some aspects of the relative insufficiency of discipline methods will be observed, as well as some youths´ ways of expression in the conflict. Moreover, it is interesting to discuss the request for reciprocity that young people demand to educative agents. Some of this topics relieves the fictional trait that usually describes the intersubjective situations at school, but that can be extended over different scenarios which regulates social issues.